Sensitivity of Global Ocean Deoxygenation to Vertical and Isopycnal Mixing in an Ocean Biogeochemistry Model. Issue 4 (14th April 2022) - Ito, T.; Takano, Y.; Deutsch, C.; Long, M. C.
Abstract: Large‐scale loss of oxygen under global warming is termed "ocean deoxygenation" and is caused by the imbalance between physical supply and biological consumption of oxygen in the ocean interior. Significant progress has been made in the theoretical understanding of ocean deoxygenation; however, many questions remain unresolved. The oxygen change in the tropical thermocline is poorly understood, with diverging projections among different models. Physical oxygen supply is controlled by a suite of processes that transport oxygen‐rich surface waters into the interior ocean, which is expected to weaken due to increasing stratification under global warming. Using a numerical model and a series of sensitivity experiments, the role of ocean mixing is examined in terms of effects on the mean state and the response to a transient warming. Both vertical and horizontal (isopycnal) mixing coefficients are systematically varied over a wide range, and the resulting oxygen distributions in equilibrated and transient simulations are examined. The spatial patterns of oxygen loss are sensitive to both vertical and isopycnal mixing, and the sign of tropical oxygen trend under climate warming can reverse depending on the choice of mixing parameters. An elevated level of isopycnal mixing disrupts the vertical advective‐diffusive balance of the tropical thermocline, increasing the mean state oxygen as well as the magnitude of the transient oxygen decline. These results provide first‐order explanations for the diverging behaviors of simulated tropical oxygen with respect to ocean mixing parameters. Key Points: Global ocean deoxygenation is sensitive to ocean ventilation primarily modulated by vertical mixing Spatial patterns of ocean deoxygenation are sensitive to both vertical mixing and isopycnal eddy stirring Oxygen‐Heat ratio remains relatively stable over a wide range of ocean ventilation parameters